PENGARUH INDEKS PEMBANGUNAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (IP-TIK), JUMLAH PENDUDUK DAN TINGKAT PENGANGGURAN TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA - Dhiya Marzuq Falah Ramadhan; Sodik Dwi Purnomo; Zumaeroh Zumaeroh (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Income inequality remains one of the foremost challenges in Indonesia's economic development, reflecting the uneven distribution of welfare across regions. This study examines the effects of the Information and Communication Technology Development Index (ICT-DI), population size, and unemployment rate on income inequality across Indonesia over the 2019–2023 period. Employing a quantitative approach, the study draws on secondary data from Statistics Indonesia (BPS) covering 34 provinces. The findings indicate that the ICT Development Index exerts a negative and statistically significant effect on income inequality, suggesting that advances in digital technology access and utilization foster a more equitable distribution of income. Population size, by contrast, demonstrates a positive yet statistically insignificant effect, implying that sheer demographic magnitude does not independently determine inequality in the absence of supportive structural conditions. The unemployment rate, meanwhile, shows a positive and significant effect, underscoring that rising unemployment tends to widen the income gap between employed and unemployed segments of the population. Accordingly, inclusive ICT development alongside robust employment creation policies should be prioritized as key instruments in reducing income inequality in Indonesia. This study is subject to several limitations, namely its reliance on three independent variables, a comparatively narrow observation window (2019–2023), and secondary data sourced exclusively from BPS, which may not fully capture the qualitative dimensions that shape income inequality.